Pengaruh Profitabilitas, Leverage, Ukuran Perusahaa Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Sub Sektor Industri Barang Konsumsi Yang Tedaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Nita Pratiwi; Jihen Ginting (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
In this study, the researchers aimed to determine the effect of Profitability , Leverage , Company Size and Sales Growth on firm value in manufacturing companies listed in Indonesia Stock Exchange in 201 6 -2018. The study population i ni is a company manufacturing sub- sector of industrial goods consumption y ang listed on the Stock Exchange in 201 6 -201 8 as much as 50 perusahaa n. The research sample was 18 companies with purposive sampling method , with quantitative research type. The data used is secondary data, the company's financial statements were obtained from www.idx.co.id., https://finance.yahoo.com, or from the company's official website. This study uses linear regression analysis techniques and uses the SPSS version 2 5 statistical test . Outcome of this study showed that partially that profitability impact on the value of the company by the value of sig 0.001. Leverage does not impact significantly on the value of the company by the value of sig 0.670. The size of the Company's influence on the value of the company by the value of sig 0,000. Growth Sales no effect on the value of the company by the value of sig 0.344. And are simultaneously profitability, leverage, size of the company and the growth of sales impact on the value of the company by the value of sig 0,000. The conclusion in this study is that partially the profitability variable has a significant effect on firm value, the leverage variable has no significant effect on firm value, the firm size variable hasa significant effect on firm value, sales growth has no significant effect on firm value, and simultaneously the variable profitability , leverage, company size, and sales growth simultaneously (jointly) affect firm value.